Prevalence of pathogenic free-living amoeba and other protozoa in natural and communal piped tap water from Queen Elizabeth protected area, Uganda. Issue 1 (December 2016) - Sente, Celsus; Erume, Joseph; Naigaga, Irene; Mulindwa, Julius; Ochwo, Sylvester; Magambo, Phillip; Namara, Benigna; Kato, Charles; Sebyatika, George; Muwonge, Kevin; Ocaido, Michael
Abstract Background Pathogenic water dwelling protozoa such asAcanthamoeba spp., Hartmannella spp., Naegleria spp., Cryptosporidium spp.and Giardia spp. are often responsible for devastating illnesses especially in children and immunocompromised individuals, yet their presence and prevalence in certain environment in sub-Saharan Africa is still unknown to most researchers, public health officials and medical practitioners. The objective of this study was to establish the presence and prevalence of pathogenic free-living amoeba (FLA), Cryptosporidium andGiardia in Queen Elizabeth Protected Area (QEPA). Methods Samples were collected from communal taps and natural water sites in QEPA. Physical water parameters were measured in situ. The samples were processed to detect the presence of FLA trophozoites by xenic cultivation, Cryptosporidium oocysts by Ziehl-Neelsen stain andGiardia cysts by Zinc Sulphate floatation technique. Parasites were observed microscopically, identified, counted and recorded. For FLA, genomic DNA was extracted for amplification and sequencing. Results Both natural and tap water sources were contaminated with FLA, Cryptosporidium spp. andGiardia spp. All protozoan parasites were more abundant in the colder rainy season except forHarmannella spp. andNaegleria spp. which occurred more in the warmer months. The prevalence of all parasites was higher in tap water than in natural water samples. There was a strong negative correlation between the presence ofAcanthamoeba spp., Hartmannella spp., Cryptosporidium spp. andGiardia spp. with Dissolved Oxygen (DO) (P  < 0.05). The presence ofCryptosporidium spp. showed a significant positive correlation (P  < 0.05) with conductivity, pH and Total Dissolved Solids (TDS); whereas the presence ofGiardia spp. had only a strong positive correlation with TDS. Molecular genotyping of FLA produced 7Acanthamoeba, 5Echinamoeba, 2Hartmannella, 1Bodomorpha, 1Nuclearia and 1Cercomonas partial sequences. Conclusions All water collection sites were found to be contaminated with pathogenic protozoa that could possibly be the cause of a number of silent morbidities and mortalities among rural households in QEPA. This implies that water used by communities in QEPA is of poor quality and predisposes them to a variety of protozoan infections including the FLA whose public health importance was never reported, thus necessitating adoption of proper water safety measures.